The Implementation of Cooperative Learning with Numbered Heads Together (NHT) Technique to Improve Students' Educational Interaction in Islamic Education - Wahyu Aji Sewoko; Ifeoma Chinyere Umeji; Martinis Yamin; Rudyn Alaldaya (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2024)
ENGLISH: The Implementation of Cooperative Learning with Numbered Heads Together Technique to Improve Students' Educational Interaction in Islamic Education SubjectsObjective: This study aims to implement the Numbered Heads Together (NHT) with a cooperative learning model to improve students' educational interaction in Islamic education. This research was conducted at SMPN 34 Mukomuko. Method: The research used a Classroom Action Research design. Data was collected through observation, documentation, and interviews. Data was analyzed using three interrelated components: reduction, display, and conclusion drawing. Results: Numbered Heads Together (NHT) technique in cooperative learning significantly improves students' educational interaction in the classroom. Conclusion: The NHT technique encourages students to actively participate, discuss, and share knowledge within the group, thus creating an inclusive and collaborative learning environment. Contribution: This research guides teachers and managers of educational institutions in designing Islamic education learning strategies by prioritizing Islamic values.INDONESIAN: Implementasi Pembelajaran Kooperatif dengan Teknik Numbered Heads Together (NHT) untuk Meningkatkan Interaksi Edukatif Siswa pada Mata Pelajaran Pendidikan Agama IslamTujuan: Penelitian ini bertujuan untuk mengimplementasikan model pembelajaran kooperatif tipe Numbered Heads Together (NHT) dalam meningkatkan interaksi edukatif siswa pada mata pelajaran Pendidikan Agama Islam. Penelitian ini dilaksanakan di SMPN 34 Mukomuko. Metode: Desain penelitian menggunakan Classroom Action Research. Pengumpulan data melalui pengamatan, dokumentasi dan wawancara. Analisis data menggunakan reduksi data. Hasil: Penggunaan teknik Numbered Heads Together (NHT) dalam pembelajaran berbasis pembelajaran kooperatif secara signifikan meningkatkan interaksi edukatif siswa di dalam kelas. Kesimpulan: Teknik NHT mendorong siswa untuk berpartisipasi aktif, berdiskusi, dan berbagi pengetahuan di dalam kelompok, sehingga menciptakan lingkungan belajar yang inklusif dan kolaboratif. Kontribusi: Penelitian ini memberikan panduan bagi guru dan pengelola Madrasah Aliyah dalam merancang strategi pembelajaran pendidikan Islam dengan mengedepankan nilai-nilai Islam.